2011
DOI: 10.1007/s11274-010-0628-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of lindane pesticide by non white- rots soil fungus Fusarium sp.

Abstract: Lindane or c-hexachlorocyclohexane (c-HCH) is a chlorinated pesticide and its toxic effects on biota necessitate its removal. Microbial degradation is an important process for pesticide bioremediation and the role of soil fungi in recycling of organic matter prompted us to study the biodegradation of lindane using fungi. This study aims at enrichment, isolation and screening of soil fungi capable of metabolizing lindane. Two Fusarium species (F. poae and F. solani) isolated from the pesticide contaminated soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(19 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Bacterial cells use organic pollutants as a sole source of carbon and nitrogen (Chen et al, 2011(Chen et al, , 2014Zhan et al, 2018b;Lin et al, 2020). Currently, a number of lindane-degrading bacterial strains have been screened, enriched, and domesticated (Table 1) (Nagpal and Paknikar, 2006), Klebsiella (Nagpal and Paknikar, 2006), Pleurotus (Dritsa and Rigas, 2013), Fusarium (Sagar and Singh, 2011), and Actinobacteria (Cuozzo et al, 2017).…”
Section: Potential Microorganisms In Lindane Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial cells use organic pollutants as a sole source of carbon and nitrogen (Chen et al, 2011(Chen et al, , 2014Zhan et al, 2018b;Lin et al, 2020). Currently, a number of lindane-degrading bacterial strains have been screened, enriched, and domesticated (Table 1) (Nagpal and Paknikar, 2006), Klebsiella (Nagpal and Paknikar, 2006), Pleurotus (Dritsa and Rigas, 2013), Fusarium (Sagar and Singh, 2011), and Actinobacteria (Cuozzo et al, 2017).…”
Section: Potential Microorganisms In Lindane Degradationmentioning
confidence: 99%
“…Lindane is still being used in some developing countries for agricultural and public health purposes due to its low cost and versatility in pest control (Abhilash and Singh, 2010). Currently, India is the largest producer and consumer of lindane in the world (Sagar and Singh, 2011). Continuous applications and indiscriminate industrial production have led to widespread lindane contamination of soils in the country (Vankar and Ramashanker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of the known isomers of HCH, c-HCH is the only one endowed with insecticidal properties and pure c-HCH (>99%) products, commonly known as lindane, have been obtained by the refining of technical-grade HCH and used extensively as inexpensive insecticides for agricultural and pharmaceutical purposes worldwide (Phillips et al, 2005;Manickam et al, 2007;Lal et al, 2010;Sagar and Singh, 2011). The global occurrence of b-HCH in ecosystems is related to: (a) the production and extensive use of technical HCH-based formulations and commercial products of lindane; (b) the improper disposal of ''HCH-muck'', which is the so-called non-insecticidal waste composed of a mixture of all HCH isomers resulting as by-products from lindane production and technical-grade HCH purification; (c) isomerization from a-HCH and c-HCH isomers (Wu et al, 1997;Willett et al, 1998;Walker et al, 1999;Wania et al, 1999;Phillips et al, 2005;Manickam et al, 2007;Lal et al, 2010;Sagar and Singh, 2011;Guillén-Jiménez et al, 2012). b-HCH has the lowest volatility and is the most recalcitrant isomer of hexachlorocyclohexane with respect to microbial degradation (Bachmann et al, 1988;Willett et al, 1998;Middeldorp et al, 2005;Phillips et al, 2005;Lal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, non-white-rot fungal species isolated from polluted sites may be better adapted to environmental and ecological soil conditions than white-rot fungi and may be better organisms for bioremediation with faster growth rates and lower temperature and oxygen requirements (Nagpal et al, 2008;Guillén-Jiménez et al, 2012). Reports on non-white-rot fungi as lindane degraders are scanty and few fungal species have been studied (Tas ßeli, 2006;Nagpal et al, 2008;Sagar and Singh, 2011;Guillén-Jiménez et al, 2012;Salam et al, 2013;Salam and Das, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation of lindane by two fungal strains isolated from contaminated soil was investigated. Although both fungi could use lindane as their sole carbon source, the results indicated that biodegradation of lindane by F. solani was slightly greater than by F. Poae(Sagar and Singh, 2011) Fuentes et al, 2011. tested the ability of pure and mixed (2 to 6) cultures of Streptomyces sp.…”
mentioning
confidence: 99%